Performance Analysis of the Brimob Training Unit (Satlat Brimob) Using a SWOT Approach - Iskandar Iskandar; Slamet Ahmad (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research aims to analyze organizational performance measurements at the Brimob Training Unit (Satlat Brimob) using the SWOT method. The study employs a descriptive analysis with a qualitative approach. The findings reveal several strategies derived from the SWOT analysis. The Strengths-Opportunities strategy involves deploying trained resources to address security needs, collaborating with agencies for suitable and renewable equipment and weapons procurement, and conducting HR training with nationally and internationally accredited agencies. The Weaknesses-Opportunities strategy includes coordinating with the Indonesian National Police (INP) Headquarters to fulfill personnel requirements according to the Personnel and Equipment Composition List (DSPP) and seeking additional budget allocations and supporting facilities. The Strengths-Threats strategy focuses on positioning trained human resources in security areas to counter disturbances from radical groups and evolving crime modes, as well as utilizing adequate equipment to prevent security threats and detect sophisticated criminal activities. The Weaknesses-Threats strategy involves assigning the best personnel to maintain security against radical groups and implementing supporting facilities with information systems to detect crime routes. The research highlights the importance of strategic resource allocation, inter-agency collaboration, and continuous improvement in training and equipment to enhance the Brimob Training Unit's organizational performance and address security challenges effectively. These findings provide valuable insights for improving the operational efficiency and effectiveness of the Brimob Training Unit in maintaining public safety and security.